STUDY OF THE CHEMICAL COMPOSITION OF INDUSTRIAL WASTEWATER - Artikov, Maksud Bakhodirovich; Allaniyazova, Mapruza Kidirbaevna; Narbaev, Oybek Kholmirzaevich (SCIENCE and SOCIETY, 2026)
The article analyzes the chemical composition of industrial wastewater entering treatment plants, the chemical content of the main pollutant components and the difference in harmful substance concentrations within them compared to the established regulatory value, methods for their determination, as well as their environmental impact using the wastewater of the region's existing licorice root processing enterprise as an example. The research results are of practical importance for improving technologies for the assessment and treatment of industrial wastewater.
Keywords: water; environment; drinking water; chemical composition; ammonia; sulfate; mineralization; chloride; nitrate; population; human; need; reasonable; norm; licorice root; enterprise; technology; wastewater